The influence of price, brand image and product quality on purchasing decisions for honda vario motorbikes (case study on Pelita Bangsa University management study program students) - Lita Alpionita; Nur' Aeni (Institute of Computer Science (IOCS), 2023)
The purpose of this study was to determine the effect of price, brand image and product quality on purchasing decisions for Honda Vario motorbikes for Pelita Bangsa University management study program students. There are several factors that generally underlie consumer considerations in buying a product or service, namely price, brand image and product quality. In this study, the research subjects are students of the Pelita Bangsa University Management Study Program, the majority of whom ride motorbikes compared to cars, and not a few have Honda Vario motorbikes. The research method used in this research is quantitative research. The population used in this study were Pelita Bangsa University students. The sampling method used by the author in this study is a non-probability sampling method with purposive sampling technique, where the sample is Pelita Bangsa University management study program students with a total of 90. The data collection method used in this study is primary data. Primary data taken is data from the answers of respondents totaling 90 respondents. The results of this study indicate that price has an impact on purchasing decisions for Honda Vario motorbikes for Pelita Bangsa University Management study program students as evidenced by the tcount> ttable value or (2.575> 1.987). This is also reinforced by the Sig value. <0.05 or (0.012 <0.05). Brand image has no effect on purchasing decisions for Honda Vario motorbikes for Pelita Bangsa University Management study program students as evidenced by the tcount value < t table or (1.232 < 1.987). This is also reinforced by the Sig value. > 0.05 or (0.221> 0.05). Product quality has an impact on purchasing decisions for Honda Vario motorbikes for Pelita Bangsa University Management study program students as evidenced by the tcount> ttable value or (4.715> 1.987). This is also reinforced by the Sig value. <0.05 or (0.000 <0.05).